Emotional context can reduce the negative impact of face masks on inferring emotions - McCrackin, Sarah D.; Ristic, Jelena (Frontiers in Psychology, 2022)
While face masks prevent the spread of disease, they occlude lower face parts and thus impair facial emotion recognition. Since emotions are often also contextually situated, it remains unknown whether providing a descriptive emotional context alongside the facial emotion may reduce some of the negative impact of facial occlusion on emotional communication. To address this question, we examined how emotional inferences were affected by facial occlusion and the availability of emotional context. Participants were presented with happy or sad emotional faces who were either fully visible or partially obstructed by an opaque surgical mask. The faces were shown either within an emotionally congruent (e.g., “Her cat was found/lost yesterday afternoon”) or neutral context (“Get ready to see the next person”). Participants were asked to infer the emotional states of the protagonists by rating their emotional intensity and valence. Facial occlusion by masks impacted the ratings, such that protagonists were judged to feel less intense and more neutral emotions when they wore masks relative to when their face was fully visible. Importantly, this negative impact of visual occlusion by mask was reduced but not fully eliminated when the faces were presented within a congruent emotional context. Thus, visual occlusion of facial emotions impairs understanding of emotions; however, this negative effect may be partially mitigated by the availability of a larger emotional context.